2016
DOI: 10.1371/journal.pone.0166271
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Functional Complementation between Grp94 and Hsp90

Abstract: Grp94 and Hsp90 are the ER and cytoplasmic paralog members, respectively, of the hsp90 family of molecular chaperones. The structural and biochemical differences between Hsp90 and Grp94 that allow each paralog to efficiently chaperone its particular set of clients are poorly understood. The two paralogs exhibit a high degree of sequence similarity, yet also display significant differences in their quaternary conformations and ATPase activity. In order to identify the structural elements that distinguish Grp94 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Hsp90 paralogs, which are expressed in different compartments of the cell 3 , have a client base involved in signaling pathways that control cell homeostasis, growth, proliferation, differentiation, and cell death. For well-studied cytosolic Hsp90 family members, which have >500 known clients 4 , co-chaperone and client binding studies have revealed a case-specific, yet broad interaction surface that recognizes remaining exposed hydrophobic patches of largely-folded or intrinsically disordered clients 3 . By contrast, details of chaperone biology and mechanism of the endoplasmic reticulum (ER)-resident paralog glucose regulated protein 94 (Grp94, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Hsp90 paralogs, which are expressed in different compartments of the cell 3 , have a client base involved in signaling pathways that control cell homeostasis, growth, proliferation, differentiation, and cell death. For well-studied cytosolic Hsp90 family members, which have >500 known clients 4 , co-chaperone and client binding studies have revealed a case-specific, yet broad interaction surface that recognizes remaining exposed hydrophobic patches of largely-folded or intrinsically disordered clients 3 . By contrast, details of chaperone biology and mechanism of the endoplasmic reticulum (ER)-resident paralog glucose regulated protein 94 (Grp94, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to differences in structure and ATP hydrolysis rates, GRP94 lacks the retinue of cochaperones characteristic of cytoplasmic Hsp90. In addition, while some GRP94 domains are able to functionally substitute for their yeast Hsp90 counterparts, the equivalent yeast Hsp90 domains fail to replace their GRP94 counterparts in client maturation assays (Maharaj et al, 2016). These observations suggest that regions of divergence between the chaperones may lead to functional differences that are key to GRP94’s adaptation to the ER.…”
Section: Introductionmentioning
confidence: 99%
“…Glycoprotein 96 (gp96, GRP94, Erp99, endoplasmin) is an endoplasmic reticulum (ER) lumen resident protein from the HSP90 family [1,2] that belongs to a set of ER chaperones originally discovered as proteins induced by glucose deprivation [3]. GRP94 often functions as a dimer providing a platform for the assembly, folding or oligomerization of loaded protein cargo [4], and its function is ATP-dependent [5].…”
Section: Introductionmentioning
confidence: 99%